2001
DOI: 10.5962/bhl.title.113964
|View full text |Cite
|
Sign up to set email alerts
|

Northern leopard frog reintroduction : Raven River - year 2 (2000) /

Abstract: SRD) for their enthusiasm, assistance and support through the 2000/2001 field season. Their efforts and assistance truly enhanced this project. I would also like to extend a sincere thank-you to the following individuals for their muchappreciated contribution of volunteer time and dedication to the reintroduction project:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…Egg mass hatching times and tadpole development rates vary with water temperature (Russell andBauer 1993, cited in Wagner 1997). Previous studies have shown that under cooler temperatures, hatching times are extended and tadpole development rates are reduced (Kendell 2001). The difference in hatching times and tadpole development rates between years in this project supported this.…”
Section: Egg Mass/tadpole Developmentsupporting
confidence: 77%
See 2 more Smart Citations
“…Egg mass hatching times and tadpole development rates vary with water temperature (Russell andBauer 1993, cited in Wagner 1997). Previous studies have shown that under cooler temperatures, hatching times are extended and tadpole development rates are reduced (Kendell 2001). The difference in hatching times and tadpole development rates between years in this project supported this.…”
Section: Egg Mass/tadpole Developmentsupporting
confidence: 77%
“…After 1 5 to 25 minutes the egg masses were transferred from the transport container into predatorproof exclosure nets, which had been previously anchored in water of a depth varying from 0.6 to 1.5 metres. The predator exclosure nets were constructed according to a design described by Kendell (2001), and they served to contain the egg masses and tadpoles and to protect them from fish and avian predators.…”
Section: Egg Mass Searches Collection and Transportationmentioning
confidence: 99%
See 1 more Smart Citation
“…Frogs were last observed above water on 24 October. Five of them were spotted east of the spillgate in two locations along the west side Kendell 2001). Because the release site was so large it was not feasible to carry out any type of intensive post-release monitoring, such as a total census of young-of-theyear frogs emerging from the pond.…”
Section: Watermentioning
confidence: 99%
“…The GPS locations were recorded along with the water temperatures. The aquatic predator exclosures were constructed according to designs provided by Kris Kendell (see Kendell 2001) and used to contain and protect the egg masses and tadpoles during the rearing process (Appendix B/Photo 1).…”
Section: Introductionmentioning
confidence: 99%